Potret Kepala Sekolah dan Problematika Era Society 5.0 - Siti Fatimah; Naila Nur Hilba; Ahmad Sabri; Rully Hidayatullah (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
This research examines the role of school principals as educational leaders in the Society 5.0 era which is characterized by rapid technological advances and demands for innovative human resources. Through a literature review, this research identifies various challenges faced by school principals, including learning transformation, curriculum development, and data management.The findings of this research conclude that school principals must have a clear vision for the future of education and be able to build collaborative relationships with diverse stakeholders to overcome the complexities of the Society 5.0 era.The importance of this research highlights the importance of developing training programs for school principals to improve skills them to face the challenges of the digital era.